2018
DOI: 10.1017/s1751731118000368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oak acorn level on colostrum composition and plasma immunoglobulin G of late-pregnant goats and their kids

Abstract: Oak acorn contains high levels of tannins which have capacity to form complexes with proteins and consequently reduce their availability and as a result it could reduce colostrum quality and immunoglobulin (Ig) synthesis. Thus, the aim of this experiment was to investigate the effects of dietary oak (Quercus persica) acorn (OA) level during the last 60 days of pregnancy on colostrum composition and plasma metabolites and IgG level of goats and their kids. In all, 24 multiparous pregnant goats (41.7±2.3 kg BW) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…In present study the dietary intervention with HT helped to decrease the serum IgG and IgM levels which might positively be associated with digestibility of protein in rats [40]. However, the lack of experimental effect of HT was observed on the serum total protein which was in agreement with the previous study [41] and showed that HT had shown non toxic effects on protein metabolism. In this study the increased water intake was also observed in PCOS rats which were also observed in various previous research trials [6]; but the experimental effect of HT was observed to decrease the water intake in rats [42].…”
Section: Discussionsupporting
confidence: 89%
“…In present study the dietary intervention with HT helped to decrease the serum IgG and IgM levels which might positively be associated with digestibility of protein in rats [40]. However, the lack of experimental effect of HT was observed on the serum total protein which was in agreement with the previous study [41] and showed that HT had shown non toxic effects on protein metabolism. In this study the increased water intake was also observed in PCOS rats which were also observed in various previous research trials [6]; but the experimental effect of HT was observed to decrease the water intake in rats [42].…”
Section: Discussionsupporting
confidence: 89%
“…However, the scope of the study did not allow for firm conclusions to be drawn regarding the higher lactose content of colostrum in the CNT cows than in the CON cows; despite this, increases in glucose production could not be excluded (Lin et al, 2016). The increased lactose content that was noted in the colostrum of CNT cows was not supported by findings reported by Jafari et al (2018), who evaluated the effects of oak acorn on the colostrum compositions of goats. This disagreement could be related to differences in methodologies and/or tannin origins and supplementation levels (Jayanegara et al, 2015).…”
Section: Discussionmentioning
confidence: 75%
“…The serum protein concentration in rams was 6.06mg/dL on average and this had a tendency (P=0.04) as compared to that of bucks (5.75mg/dL on average).There was a tendency (P=0.07) in bucks fed T4 as compared to bucks fed T2 and rams fed T3 and control diets. The plasma urea concentration is an indicator of protein degradation in the rumen (Jafari et al, 2018), thus the absence of the effect of dietary treatment on serum urea concentration in the current study may be related to the absence of the effect of treatments on CP digestibility coefficient.…”
Section: Ammonia-nitrogen (Nh3-n)mentioning
confidence: 76%
“…This species is distributed in the regions of cool temperate to tropical latitudes in Asia, Americas, North Africa, and Europe. (Jafari et al, 2018). Oak twigs and leaves are commonly grazed by animals or loped to use as fodder for livestock during feed shortage periods (Singh et al, 1996).…”
Section: Introductionmentioning
confidence: 99%